Optimizing Competitive Advantages in Amtsilati Flagship Programs: A Strategic Approach to Enhance Islamic Boarding Schools' Competitiveness - Sopwandin, Iwan; Baits, Abdul; Rostiana, Isep Nendri (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2025)
This study aims to analyze the efforts made by Ansoriyah Islamic Boarding School to increase competitiveness through competitive advantages in the Amtsilati flagship program. The research method used is qualitative with a descriptive analysis approach. Data collection techniques are carried out through participatory observation, structured interviews, and documentation studies. The data analysis in this study includes data condensation, data presentation, and conclusion. Testing the validity of the data is carried out with diligent observation, triangulation, and adequacy of reference materials. The results of this study indicate that Ansoriyah Islamic Boarding School seeks to achieve competitive advantage through the Amtsilati flagship program consisting of: 1) Amtsilati quality as a fast method of yellow books used by various Islamic boarding schools in Indonesia, in addition, Amtsilati teachers are direct graduates of Amtsilati central Islamic boarding schools; 2) Minimal costs incurred to be able to participate in the Amtsilati program; 3) Amtsilati completion time is not too long, and; 4) Amtsilati flexibility, one example of which is the increase in the level of the book which can be carried out at any time according to the ability of the students.